The comprehensive guide to special education law : over 400 frequently asked questions and answers every educator needs to know about the legal rights of exceptional children and their parents - Giuliani, George A., 1938- (Jessica Kingsley Publishers, 2012)
It is vital for all professionals in the field of education to have a practical understanding of the laws that are in place to protect the children with whom they work. The Comprehensive Guide to Special Education Law is a detailed yet accessible introduction to federal law as it applies to the rights of children with special needs. Written in a user-friendly question and answer format, the book covers all of the key areas of special education law including parental rights of participation, the legal right to Free Appropriate Public Education (FAPE) and related services, and the complex issues.